Myocarditis Following Coronavirus Disease 2019 mRNA Vaccine: A Case Series and Incidence Rate Determination. (3rd November 2021) - Perez, Yalile; Levy, Emily R; Joshi, Avni Y; Virk, Abinash; Rodriguez-Porcel, Martin; Johnson, Matthew; Roellinger, Daniel; Vanichkachorn, Greg; Charles Huskins, W; Swift, Melanie D
Abstract: Background: Myocarditis following coronavirus disease 2019 (COVID-19) mRNA vaccines (Pfizer-BioNTech and Moderna) has been increasingly reported. Incidence rates in the general population are lacking, with pericarditis rather than myocarditis diagnostic codes being used to estimate background rates. This comparison is critical for balancing the risk of vaccination with the risk of no vaccination. Methods: A retrospective case series was performed using the Mayo Clinic COVID-19 Vaccine Registry. We measured the incidence rate ratio (IRR) for myocarditis temporally related to COVID-19 mRNA vaccination compared with myocarditis in a comparable population from 2016 through 2020. Clinical characteristics and outcomes of the affected patients were collected. A total of 21 individuals were identified, but ultimately 7 patients met the inclusion criteria for vaccine-associated myocarditis. Results: The overall IRR of COVID-19–related myocarditis was 4.18 (95% confidence interval [CI], 1.63–8.98), which was entirely attributable to an increased IRR among adult males (IRR, 6.69; 95% CI, 2.35–15.52) compared with females (IRR 1.41; 95% CI, .03–8.45). All cases occurred within 2 weeks of a dose of the COVID-19 mRNA vaccine, with the majority occurring within 3 days (range, 1–13) following the second dose (6 of 7 patients, 86%). Overall, cases were mild, and all patients survived. Conclusions: Myocarditis is a rare adverse event associated with COVID-19 mRNA vaccines. It occurs in adult males with significantly higher incidence than in the background population. Recurrence of myocarditis after a subsequent mRNA vaccine dose is not known at this time. Abstract : The incidence rate ratio of myocarditis following coronavirus disease 2019 mRNA vaccination is significantly increased for adult males. Most cases occurred within 3 days (range, 1–13) following the second vaccine dose. Cases were mild, and there were no deaths.